Point cloud computing algorithm on object surface based on virtual reality technology. (29th June 2021) - Zhang, Wanyi; Fu, Xiuhua; Li, Wei
Abstract: Virtual reality technology is also known as VR technology. Accurately acquiring the three‐dimensional model of the point cloud on the surface of an object is a key part of virtual reality technology, and is also a research hotspot of virtual reality technology. The purpose of this article is to study the object surface point cloud computing algorithm based on virtual reality technology and its application problems and to solve the problems in the virtual reality technology object surface point cloud data algorithm, by reconstructing the geometry of the object surface in VR technology. The calculation rules at the time of data acquisition have been carried out in detailed research on the point cloud space carving algorithm based on the surface of multi‐eye visual objects. The research results show that the point cloud space carving algorithm on the surface of the virtual reality technology has a high degree of independence and the algorithm is very flexible. Compared with other algorithms, it reduces the operation steps by 35%, the 3D effect is increased by 21%, and the operation cost is reduced by 30%. The object surface point cloud computing algorithm based on virtual reality technology can greatly improve the computing efficiency, compared with the traditional two‐dimensional visual image integration algorithm, the efficiency is increased by 35%, and the computing accuracy in virtual reality technology is the same as the traditional two The accuracy of the integrated algorithm of dimensional visual pictures is improved by 44% compared to the accuracy. The experimental results verify the feasibility of applying the spatial carving algorithm to the three‐dimensional reconstruction of point cloud data on the surface of virtual reality technology objects.